Ukrainian textbooks in the aspect of gender balance (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article is devoted to the analysis of Ukrainian textbooks in the aspect of gender balance. In particular it pays attention to the frequency of use of the works of famous men writers / women writers, peculiarity of reconstruction of men / women’s images on the pages of the  textbooks, availability of materials, which subject has gender color, etc.
Keywords: gender analysis; gender disparity; gender stereotypes; gender balance